Medicinal plants used in gynecological procedures in Uganda - Tenywa, Mercy Gladys; Agaba, Amon; Ogwang, Patrick Engeu; Tolo, Casim Umba; Ajayi, Clement Olusojia; Katuura, Esther (Medicinal plants used in gynecological procedures in Uganda, 2020)
Distress and pains among other gynecological challenges mothers go through during childbirth result in mortality. This has compelled people particularly in developing countries to use traditional medicine to induce birth due to lack of more effective alternatives. In Uganda, from time immemorial most child birth and pregnancy related problems have been solved using medicinal plants as a primary alternative to conventional drugs. Although research has been done to document and validate effectiveness of these plants, it is not compil ed for communication to the wider community. This study, therefore, reviewed the medicinal plants used in Uganda for easing childbirth. The study collated and documented medicinal plants used by Traditional Birth Attendants and Traditional Health Practitioners to induce labor and ease child birth in local communities in Uganda and show the gaps that need to be investigated. The available literature on medicinal plants used in Uganda for childbirth were selected from reputable journals using citation databases including Google Scholar, Institute for Scientific Information, PubMed, Scopus, Hinari, and Scientific Information Database among others. Asteraceae, Fabaceae, and Lamiaceae, respectively were the most cited for gynecological uses by various local communities in Uganda. The commonly reported species were Laggera alata Sch. Bip., Tagetes minuta L, Clitoria ternatea Linn and Ocimum lamiifolium Hochst ex Benth among others. Authors were also determined to ascertain scientific evidence against analgesic, anti-inflammatory, oxytocic and phytochemical properties of the selected plant species.
Keywords: Childbirth; Medicinal plant; Gynecology; Uganda